Physiology and Pathophysiology of Musculoskeletal Aging - Ali Mobasheri (Frontiers Research Topics, 2015)
We live in a world with an ever-increasing aging population. This aging population is predicted to place a huge financial burden on healthcare systems around the world. Understanding healthy ageing is a key research priority, along with a better understanding of the pathophysiology of ageing that occurs in a number of age related diseases, such as arthritis. By gaining a better understanding of healthy musculoskeletal ageing we can provide better care and new therapies for common musculoskeletal problems. This Research Topic is intended to bring together basic researchers and clinicians working in the broad area of musculoskeletal ageing. The topic includes mechanisms of healthy ageing in the musculoskeletal system, which we define as skeletal muscle and the synovial joint, particularly constituent structures including articular cartilage, subchondral bone tendon and ligament. A particular focus of this Research Topic is dietary modulation of musculoskeletal ageing.